2001
DOI: 10.1007/s004210100399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training in humans on neck muscle performance, and electromyogram power spectrum changes

Abstract: The purpose of this study was to quantify the neuromuscular cervical adaptations to an 8 week strength training programme. Seven healthy men, with no pathological conditions of the neck, performed a lateral flexion isometric resistance-training programme three times a week. The training sessions consisted of one set of ten contractions, each of 6 s duration, at 60% of the predetermined maximal voluntary isometric torque (MVTim) (warm-up) and two sets of eight contractions, each of 6 s duration, at 80% MVTim. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Gains in isometric strength following rehabilita- Craniocervical Flexor Muscle Performance* tion have been correlated with increases in cross-sectional area of neck muscles. 5,31 However, this may not explain the gains in MVC observed for both groups in this study (TABLE), particularly for the CCFEx group, who only ever performed relatively low-intensity exercise. Gains in MVC following only 6 weeks of therapeutic exercise, as performed in this study, may be more associated with neuromuscular adaptations such as greater synchronization of motor units, 4,23 altered sensitivity of muscle receptors, 20 and reduced recruitment of nonprimary muscles.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Gains in isometric strength following rehabilita- Craniocervical Flexor Muscle Performance* tion have been correlated with increases in cross-sectional area of neck muscles. 5,31 However, this may not explain the gains in MVC observed for both groups in this study (TABLE), particularly for the CCFEx group, who only ever performed relatively low-intensity exercise. Gains in MVC following only 6 weeks of therapeutic exercise, as performed in this study, may be more associated with neuromuscular adaptations such as greater synchronization of motor units, 4,23 altered sensitivity of muscle receptors, 20 and reduced recruitment of nonprimary muscles.…”
mentioning
confidence: 63%
“…18,21,32,33 Although both exercise programs had some characteristics specific to the isometric dynamometry tests, neither were identical, particularly with regard to characteristics such as joint angles, velocity, duration, and intensity of CCF muscle contractions. Additionally, there is also some evidence that isometric tests of muscular function are not sensitive to dynamically induced training adaptations, 31,39 as may have been expected with both exercise programs.…”
mentioning
confidence: 99%
“…Daily SBT with PSV 7/0 [pressure support of 7 cmH 2 O and no positive endexpiratory pressure (PEEP)] is a reproducible effort where EAdi can easily be measured. A mean respiratory effort *60% of the value developed during the inspiratory effort could be adapted to prevent respiratory muscle fatigue or limit the incidence of over-assistance [13,14]. Patients in whom PSV 7/0 can be maintained for two consecutive hours are usually extubated [1].…”
Section: Introductionmentioning
confidence: 99%
“…It was the intention of the CCFD testing protocol to challenge and measure the isometric fu nction of this muscle group over a range of contraction intensities (low to maximal) similar to intensities which could feasibly be fa ced in ordinary daily fu nction. Based on this ideal as well as the evidence provided previously, (Falla et al 2003b ;Gogia and Sabbahi 1994), and at moderate loads (50-60% of IMVC) (Falla et al 2003b ;Gogia and Sabbahi 1994;Randlov et al 1998;Portero et al 2001) have been previously reported for cervical muscle fat igue studies. Studies investigating muscle fa tigue in other regions of the body have also used similar sub-maximal sustained contraction intensities (Duchateau and Hainaut 1993;Duchateau et al 2002;Hunter et al 2002;Hunter et al 2004).…”
Section: Intensity Of Contraction Loadsupporting
confidence: 67%